The Influence of Product Design, Social Media Promotion, and Customer Reviews on the Purchase Decision of Margo Glass Gallery Sukoharjo Decoration Mirror Products - Anggid Setyo Jatmiko; Sudarwati Sudarwati; Istiatin Istiatin (STIE PENA, 2026)
This study aims to analyze the influence of product design, social media promotion, and customer reviews on purchasing decisions of decorative mirror products at Margo Glass Gallery Sukoharjo. This research uses a quantitative approach with a purposive sampling technique. The population of this study consists of consumers who have purchased decorative mirror products at Margo Glass Gallery Sukoharjo. The research sample consists of 100 respondents selected based on specific criteria relevant to the research objectives. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the assistance of IBM SPSS software. The independent variables in this study are product design, social media promotion, and customer reviews, while the dependent variable is purchasing decision. The results indicate that product design has a positive and significant effect on purchasing decisions, social media promotion has a positive and significant effect on purchasing decisions, and customer reviews have a positive and significant effect on purchasing decisions. Simultaneously, product design, social media promotion, and customer reviews have a positive and significant effect on purchasing decisions of decorative mirror products at Margo Glass Gallery Sukoharjo.Keywords : Product Design, Social Media Promotion, Customer Reviews, Purchasing Decision